The Role of the International Atomic Energy Agency in Maintaining Nuclear Peace and Non-proliferation Regime in the 21st Century - Tomasz Młynarski (Politeja, 2017)
The article is an attempt to explain the IAEA’s critical role in ensuring global nuclear safety and on the global nuclear governance system. The objective of the Agency’s operation is promotion of the peaceful use of nuclear energy, including the use of energy to produce electricity, along with establishment of a system of safeguards to ensure that the countries do not use the peaceful assistance for military purposes.The aim of the article is to present the principles of the internationalsystem of nuclear safeguards and the role of the IAEA in maintaining nuclear peace and nuclear challenges of non-proliferation regime reform. The duality of nuclear technology (dual use) causes the need of strengthening the competence-control and institutional resources of the IAEA. It is necessary to oblige the Member States to cooperate with the Agency’s inspectors. The Agency should also develop a procedure to standardize the rules, structure, and legal restrictions. In addition the UN Security Council should react faster in the case of non-compliance detection. A separate issue is the internationalization of the fuel cycle.